Screened toilet, bathing and menstruation units for the earthquake response in NWFP, Pakistan - Jamila Nawaz; Shamma Lal; Saira Raza; Sarah House (2006)
In water and sanitation interventions, sensitivity is required for the particular needs of communities when women live in seclusion. In these communities female-headed households may have restricted access to relief supplies and restricted opportunities to make their needs known. Additional screening around water and sanitation facilities can help to provide additional privacy for women and men living in camp environments in emergency settings.